Pelatihan Pemanfaatan Artificial Intelligence dan Canva bagi Dosen Fakultas Kesehatan Masyarakat Universitas Tadulako - Perdana, Fachruddin; Bohari, Bohari (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
AI training is very important for teaching staff in higher education to equip themselves with the knowledge and skills to utilize AI to improve the quality of learning, provide accurate feedback, and promote effective student engagement. This training aimed to improve the knowledge and skills of public health lecturers at Tadulako University in the utilization of artificial intelligence (AI) and Canva. The training was conducted using lectures, practices, and discussions. The training participants were 16 lecturers at the Faculty of Public Health, Tadulako University. The training materials covered AI Bard, Gamma APP AI, CANVA, Chat GPT, and Jenni AI. After the training, all participants were able to create accounts on each of the applications and were able to practice them. Participants were also able to apply AI and Canva for teaching, research, and other needs. The training was able to improve the knowledge and skills of public health lecturers at Tadulako University in the utilization of AI and Canva. AI and Canva can be useful tools to support teaching, research, and other activities. Using AI wisely can improve the accuracy and usefulness of the information provided by AI in educational media. This can help both teachers and students learn more effectively and efficiently.